2013
DOI: 10.1128/genomea.00252-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Herbaspirillum huttiense subsp. putei IAM 15032, a Strain Isolated from Well Water

Abstract: Here we report the one-scaffold draft genome of Herbaspirillum huttiense subsp. putei strain 7-2T (IAM 15032), which was isolated from well water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…GW103 (23), Os34 (17), Os45 (18), IAM 15032 (19), CF444, YR522 (3), and JC206 (7) showed that all strains harbor genes for ammonium assimilation and cobalt-zinc-cadmium resistance. The genes for denitrification were found only in strains RV1423, GSF30 T , Os34, Os45, and SmR1.…”
Section: Genome Announcementmentioning
confidence: 99%
See 2 more Smart Citations
“…GW103 (23), Os34 (17), Os45 (18), IAM 15032 (19), CF444, YR522 (3), and JC206 (7) showed that all strains harbor genes for ammonium assimilation and cobalt-zinc-cadmium resistance. The genes for denitrification were found only in strains RV1423, GSF30 T , Os34, Os45, and SmR1.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Only four Herbaspirillum genomes (those of H. lusitanum P6-12 [ 16 ], H. seropedicae Os34 [ 17 ] and Os45 [ 18 ], and H. huttiense subsp. putei IAM 15032 [ 19 ]) harbor two gentisate dioxygenase genes, and RV1432 harbors four gentisate dioxygenases.…”
Section: Genome Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequenced Herbaspirillum species include plant growth promoting soil bacteria ( HGW103 ) from the rhizosphere of the grass Phragmites australis (Lee et al, 2012), isolates ( HlP6-12 ) from the root nodules of Phaseolus vulgaris (Weiss et al, 2012), strains ( HCF444 and HYR522 ) colonizing poplar (Brown et al, 2012), a strain ( HhIAM ) isolated from Japanese well water (De Souza et al, 2013) and an isolate ( HJC206 ) from human fecal flora (Lagier et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…De Souza et al [32] demonstrated the decrease of in vitro phosphate solubility and minimization of acetylene (low reduction in acetylene) in rice shoots by bacteria, including Herbaspirillum sp., Burkholderia sp., Pseudacidovorax, and Rhizobium sp. Therefore, non-N 2 fixation growth promotion mechanisms include an IAA development and improved nutrient balanced absorption.…”
Section: Relationship Between Pgpb and Rice Production Under Nutrientmentioning
confidence: 99%